2017
DOI: 10.1002/chem.201701749
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Group 13 Cyanides

Abstract: What was the inspiration for this cover design?When we received the invitation to submit ac over art, we immediately thought about the web comic "Cyanide &H appiness," written and illustrated by Rob Denbleyker,K ris Wilson, Dave McElfatrick, and Matt Melvin, and published on explosm.net. We are big fans of the often dark and surrealistic comics and wanted to incorporate it into the cover art. Luckily,t he people from C&H were okay with us using some of their characters. The inspiration behind the cyanide work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This is in good agreement with theoretical calculations made for the [Ga(CN) 4 ] − anion. 76 We believe that this effect is due to the T d symmetry of the anion and weak charge separation between atoms in the anion. A toluene solution of paramagnetic compound 5 revealed a resolved isotropic EPR spectrum.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is in good agreement with theoretical calculations made for the [Ga(CN) 4 ] − anion. 76 We believe that this effect is due to the T d symmetry of the anion and weak charge separation between atoms in the anion. A toluene solution of paramagnetic compound 5 revealed a resolved isotropic EPR spectrum.…”
Section: ■ Introductionmentioning
confidence: 98%
“…h i b i t e d .structural data on tetracyanogalates are rather limited: CCDC exhibits data on [Et 4 N][mesGa(CN) 3 ],90 [PPh 4 ][Ga(CN) 4 ], [(bipy) 2 Ga(CN) 2 ][Ga(CN) 4 ],76 and [Ga(CN) 3 (py) 2 ],76,91 while also a few related structures Li[Ga(CN) 4 ], Cu[Ga-(CN) 4 ],92 Ga(CN) 393 are not registered with CCDC. Thegeometry of the tetrahedral solvate-separated [Ga(CN) 4 ] − ion with average C−N 1.154 Å and average Ga−C 1.919 Å interatomic distances were in excellent agreement with the parameters of the anion in [PPh 4 ][Ga(CN) 4 ] [C−N 1.145(2) Å; Ga−C 1.970(1) Å].…”
mentioning
confidence: 99%
“…11−14 Following the above halides, it could be expected that aluminum cyanides might be observed, since polymeric [Ga(CN) 3 ] has been prepared and characterized by X-ray powder diffraction and the [Ga(CN) 4 ] anion has been synthesized with the [PPh 4 ] counterion. 15,16 B3LYP calcu-lations have shown that donor−acceptor complexes between nitriles or isonitriles and Al, Ga, or In hydrides or chlorides react to form monomeric cyanides and larger ring species. 17 However, TZ2P+f CCSD(T) quantum mechanical methods have reported that AlNC is 23 kJ/mol lower in energy than AlCN.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The EC 6 coordination skeletons of the investigated complexes adhere closely to the octahedral symmetry (Figures –) with only small deviations in the interligand angles of no more than 3.80(6) and 2.32(6)° from the ideal geometry of 90 and 180°, respectively, which is ascribed to the differences in the packing imposed by the crystal systems ( 1 , orthorhombic; 2 and 3 , monoclinic, Figure ). The cyanido ligands adopt the essentially linear end-on-C coordination (κ­(C)) mode that has been observed previously for other p -block complexes with coordination centers of groups 13 and 15. , Structure models tested during crystallographic structure refinement that feature isocyanido ligands E­(CN) x (NC) y 2– all were significantly inferior in predicting the diffraction data, leading to substantially increased disagreement factors ( R ).…”
Section: Resultsmentioning
confidence: 78%
“…In group 14, they take the form of EL 4 and EL 6 2– (E = Si–Pb, L = N 3 , NO 3 , NCO, NCS, NCSe). However, there are only very few homoleptic cyanido complexes. This group of complexes is restricted to coordination centers of the less electronegative elements in groups 13 and 15 as P­(CN) 3 , Ga­(CN) 4 – , E­(CN) 5 2– (E = In, Tl, Sb, Bi) and Bi­(CN) 6 3– . In group 14, the set of known complexes consist of the E­(CN) 4 type (E = Ge, Sn), for which, apart from in situ 119 Sn NMR spectral data for the Cl/CN ligand exchange to form Sn­(CN) 6 2– , little analytical data is available. CN ligands possess a comparably low oxidation potential and this effects, for instance, the low thermal stability of P­(CN) 5 which readily eliminates cyanogen at ambient temperature to form P­(CN) 3 . The related P­(CN) 6 – complex, on the other hand, is thought to be stabilized by hypercoordination.…”
Section: Introductionmentioning
confidence: 99%